Tanggung Jawab Yang Lahir Dari Kewajiban Atas Kesehatan Masyarakat Di Masa Pandemi Covid-19 Dalam Perspektif HAM (Hak Asasi Manusia) - Nurika Falah Ilmania; Benny Krestian Heriawanto; Pinastika Prajna Paramita (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2022)
Covid-19 is a crucial health issue, as a right that must be fulfilled because it is one of human rights and the state has responsibility for public health in the form of promotive, preventive, curative and rehabilitative activities, especially in the era of covid 19. knowing the position of public health as part of human rights and the responsibility of the State for the fulfillment of health during the Covid-19 period based on the perspective of Law Number 39 of 1999 concerning Human Rights jo. Health Law Number 36 Year 2009 concerning Health. This research is a normative juridical research, with a statutory approach and a conceptual approach using legal materials in the form of legislation and some relevant literature. The technique of collecting legal materials is carried out by literature study activities using legal materials analysis techniques in the form of grammatical, systematic, and teleological. Interpretations.